Genome analysis of the staphylococcal temperate phage DW2 and functional studies on the endolysin and tail hydrolase - Keary, Ruth (Landes Bioscience, 2014)
This study describes the genome of temperate Siphoviridae phage DW2, which is routinely propagated on Staphylococcus aureus DPC5246. The 41941 bp genome revealed an open reading frame (ORF1) which has a high level of homology with members of the resolvase subfamily of site-specific serine recombinase, involved in chromosomal integration and excision. In contrast, the majority of staphylococcal phages reported to date encode tyrosine recombinases. Two putative genes encoded by phage DW2 (ORF15 and ORF24) were highly homologous to the NWMN0273 and NWMN0280 genes encoding virulence factors carried on the genome of ϕNM4, a prophage in the genome of S. aureus Newman. Phage DW2 also encodes proteins highly homologous to two well-characterized Staphylococcus aureus pathogenicity island derepressors encoded by the staphylococcal helper phage 80α indicating that it may similarly act as a helper phage for mobility of pathogenicity islands in S. aureus. This study also focused on the enzybiotic potential of phage DW2. The structure of the putative endolysin and tail hydrolase were investigated and used as the basis for a cloning strategy to create recombinant peptidoglycan hydrolyzing proteins. After overexpression in E. coli, four of these proteins (LysDW2, THDW2, CHAP(E1-153), and CHAP(E1-163)) were demonstrated to have hydrolytic activity against peptidoglycan of S. aureus and thus represent novel candidates for exploitation as enzybiotics.